Pengaruh Motivasi Belajar dan Tingkat Kecemasan Terhadap Prestasi Belajar IPA Siswa MtsN. 2 Konawe Selatan - Halmuniati Halmuniati; Hasiati Hasiati; La Wui; Faizah Binti Awad (IAIN Kendari, 2020)
This article is a quantitative study with a survey method that aims to find out and describe (1) the effect of learning motivation on science learning achievement; (2) the effect of anxiety level on science learning achievement; and (3) the effect of jointly learning motivation and anxiety levels on the learning achievement of Natural Sciences. This research was conducted at MTs Negeri 2 Konawe Selatan, Southeast Sulawesi, Indonesia. Data collection techniques using questionnaires and documentation. The validity of the instrument uses the Product Moment formula and the reliability of the instrument uses the Cronbach Alpha formula. Data analysis techniques used include the first and second hypothesis testing with simple regression analysis and the third hypothesis test with multiple regression analysis. The results showed that: (1) there was a positive and significant influence between learning motivation on science learning achievement, proved Fcount = 6.59 and Ftable = 4.034; (2) there is a positive and significant influence between the level of anxiety on the learning achievement of science proven Fcount = 4.967 and Ftable = 4.034; (3) there is a positive and significant influence together learning motivation and anxiety level on the learning achievement of science proven Fcount = 3.301> Ftable = 3.187. The coefficient of determination rsquare (R2) of 0.088 shows the magnitude of the effective contribution together at 8.8% and there are still 91.2% which is influenced by other variables not discussed in this study.Keywords: Learning Motivation, Anxiety Level, Science Learning Achievement.